Enhancing Creative Thinking in Electrochemistry through a Science Literacy Integrated STEM-PBL Model - Sutiani, Ani; Dibyantini, Ratu Evina; Nst., Mutiara Agustina; Sari, Dwy Puspita (Jurnal Tadris Kimiya, 2025)
Creative thinking is an essential learning outcome in undergraduate chemistry education, particularly in electrochemistry, where students are required to integrate conceptual understanding with problem solving and real world applications.  Integrating science literacy within a Science, Technology, Engineering, and Mathematics–Problem Based Learning (STEM-PBL) framework offers a practical instructional approach to address this challenge by situating electrochemical concepts in authentic problem contexts. This study analysed the effectiveness of a science literacy integrated STEM-PBL model in enhancing undergraduate students’ creative thinking skills in an electrochemistry course. A quantitative quasi experimental design was employed, involving an experimental group taught using the science literacy integrated STEM-PBL model and a control group receiving traditional instruction. Students’ creative thinking skills were measured before and after instruction using a validated assessment instrument. Instructional effectiveness was evaluated by comparing normalized gain (N-gain) scores between the two groups. The results show that students who participated in the STEM-PBL learning environment achieved a substantially higher N-gain score (75.47%) than those in the control group (49.96%). These findings indicate that integrating science literacy into STEM-PBL activities significantly enhances students’ creative thinking skills in electrochemistry learning. The results have important implications for chemistry instruction. They suggest that incorporating science literacy oriented, problem based STEM activities can provide instructors with an effective strategy to promote creative thinking and deepen students’ understanding of electrochemical concepts. This approach may support the design of more engaging and meaningful electrochemistry learning experiences in undergraduate chemistry classrooms.